2013
DOI: 10.1093/infdis/jit416
|View full text |Cite
|
Sign up to set email alerts
|

Faster Progression to AIDS and AIDS-Related Death Among Seroincident Individuals Infected With Recombinant HIV-1 A3/CRF02_AG Compared With Sub-subtype A3

Abstract: Our results show that there are differences in disease progression between HIV-1 A-like subtypes/CRFs. Individuals infected with A3/02 have among the fastest progression rates to AIDS reported to date. Determining the HIV-1 subtype of infected individuals could be important in the management of HIV-1 infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
41
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 38 publications
4
41
0
1
Order By: Relevance
“…Studies in East Africa, where subtypes A and D cocirculate, have established that subtype D is associated with faster disease progression than subtype A (10-13). There is also evidence that recombinant forms have a higher rate of progression to AIDS than does subtype A (10,14), although this was not observed in another study (12). There are conflicting reports regarding the rate of disease progression of subtype C relative to that of other subtypes (12,(15)(16)(17)(18).…”
mentioning
confidence: 97%
“…Studies in East Africa, where subtypes A and D cocirculate, have established that subtype D is associated with faster disease progression than subtype A (10-13). There is also evidence that recombinant forms have a higher rate of progression to AIDS than does subtype A (10,14), although this was not observed in another study (12). There are conflicting reports regarding the rate of disease progression of subtype C relative to that of other subtypes (12,(15)(16)(17)(18).…”
mentioning
confidence: 97%
“…[6][7][8] Although studies have indicated that subtype differences may not have an effect on the response to cART, particularly in HIV-1 group M strains, 9,10 recombinant strains may complicate the course of HIV infection. 11 Studies have implicated globalization and the movement of people from different geographic areas in the increasing rise in recombinant HIV strains. 2,12 In South Africa, HIV-1 subtype C has been reported to be the predominant strain.…”
mentioning
confidence: 99%
“…8,[16][17][18] Monitoring the genetic diversity of circulating HIV strains has been encouraged to generate information on patient management and even vaccine strategies. 3 Recently, Palm et al 11 demonstrated increased risk of AIDS and AIDS-related death in individuals infected with recombinant strain HIV-1 A3/CRF02_AG. The recombinant virus was found to be more virulent causing AIDS and AIDSrelated death between 5.0 and 8.0 years from the time of seroconversion.…”
mentioning
confidence: 99%
See 2 more Smart Citations